Management of Chronic Pericoronitis of Lower Third Molars with Periodontal Operculectomy Surgical Approach (Case Report) - Frita Ferlita Shafri Djohan; Viona Hartika Yusma; Rika Nurmalasari Nasution (Sean Institute, 2022)
Pericoronitis is an acute or chronic periodontal inflammation around the crown of a partially erupted mandibular third molar.A 24-year-old female patient came with a complaint of pain in the lower right lower back tooth for the past three months, disturbing her eating and making her feel uncomfortable. Extraoral examination revealed no abnormalities in the patient and intraoral examination revealed soft tissue covering the occlusal portion of tooth 48 which had partially erupted. Operculectomy was performed at region 48 using a scalpel and blade to eliminate pericoronitis. The prognosis in this case is good. Treatment results showed soft tissue healing within 1 month in accordance with the expected prognosis